PENGARUH CITRA MEREK DAN INOVASI PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK GOOD DAY PADA GENERASI Z DI KOTA SURABAYA - Mohammad Nur Rachman Arif; Hery Pudjoprastyono (Universitas Sarjanawiyata Tamansiswa, 2025)
This study aims to analyze the effect of brand image and product innovation on purchase decisions of Good Day instant coffee products among Generation Z in Surabaya City. The background of this research is based on the increasing competition in the ready-to-drink beverage industry and the changing consumption behavior of young generations who view coffee not only as a functional need but also as part of their lifestyle. A strong brand image and relevant product innovation are considered capable of enhancing consumer preference and loyalty toward a brand. This research employs a quantitative approach with a purposive sampling technique involving 100 respondents who are Good Day consumers from Generation Z. Data were collected through an online questionnaire and analyzed using Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The results show that brand image has a positive and significant influence on purchase decisions, meaning that the better the consumer’s perception of the Good Day brand, the higher the purchase decision. Furthermore, product innovation also has a positive and significant influence on purchase decisions, indicating that the variety of flavors and innovative packaging of Good Day successfully attract consumer interest and strengthen their purchasing decisions.